Low-noise integrated balanced SIS mixer for 787–950 GHz. (30th November 2016) - Fujii, Yasunori; Kojima, Takafumi; Gonzalez, Alvaro; Asayama, Shin'ichiro; Kroug, Matthias; Kaneko, Keiko; Ogawa, Hideo; Uzawa, Yoshinori
Abstract: We developed a low-noise, compact, balanced superconductor–insulator–superconductor (SIS) mixer, operating in the 787–950 GHz radio frequency range. A waveguide mixer block was designed to integrate all the key components, such as a radio frequency (RF) 90° hybrid coupler, two identical SIS mixer chips, bias-tees, and an intermediate frequency power-combiner. The RF waveguide 90° hybrid coupler consists of branch lines with wide slots optimized by numerical simulation, for ease of fabrication. The balanced mixer was installed into a cartridge type receiver, originally developed for the Atacama Large Millimeter/submillimeter Array Band 10 (787–950 GHz). The receiver demonstrated double sideband noise temperatures of approximately 200 K for most of the band, without any correction for loss in front of the receiver. The local oscillator noise rejection ratio was estimated to be more than 15 dB within the measured frequency range.